Medicine, body, mind and dissidence - Rodríguez Allen, Ana (2021)
his article discusses the strategies that people use to seek help with their ailments. It is focused on one of the existing healing options in Costa Rica, which the WHO classifies as therapies that integrate body and mind, such as meditation or hypnosis, and located outside of conventional medicine. It resorts to the works of thinkers who have in common the study of the mind, the body and medicine; all, from their different fields of knowledge, propose guidelines for action to dismantle the false mind-body dichotomy. In addition, it shows that the coherence between both dimensions produces health, since the contradictions in affective life generate diseases. This writing does not include detailed discussions of the philosophical categories expressed by its authors, it is enough for our purpose to include the most notable of their thought, not what is said with exactness, but what is suggested and provoked in others regarding the mind, the perceptions, the self or consciousness. Although some of the cited texts may be surprising to certain readers, it is not a question of adhering to any current, but rather of seeking lines of action that allow maintaining a healthy condition in all areas of life.